Assessment of Technical Condition of an Accumulator Common Rail Injector by Temperature of its Units - Ildar Gabitov; Andrei Negovora; Azamat Valiev; Vladimir Ilin; Danila Plotnikov; Mahmut Razyapov (Communications - Scientific letters of the University of Zilina, 2021)
This paper presents a method for the vehicle speed estimation with a Fuzzy Logic based algorithm. The algorithm acquires the measurements of the yaw rate, steering angle, wheel velocities and exploits a set of five Fuzzy Logics dedicated to different driving conditions. The technique estimates the speed exploiting a weighted average of the contributions provided by the longitudinal acceleration and the credibility assigned by the Fuzzy Logics to the measurements of the wheels’ speed. The method is experimentally evaluated on an all-wheel drive electric racing vehicle and is valid for the front and rear wheel drive configurations. The experimental validation is performed by comparing the obtained estimation with the result of computing the speed as the average of the linear velocity of the four wheels. A comparison to the integral of the vehicle acceleration over time is reported.